Study of the relationship of cavitation erosion activity and cavitation noise intensity - V. S. Minchuk; A. Yu. Perkhunova; A. V. Kotukhov; N. V. Dezhkunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The study of the erosion activity of cavitation is of considerable interest for clarifying the mechanism of the effect of cavitation on biological tissues and cells. This paper proposes an improved technique for assessing the erosion activity of acoustic cavitation. The results of testing this technique in relation to the problem of studying the distribution of erosion activity in the cavitation region, generated by a radiator with a rod waveguide, are presented. The experiments were carried out using a submersible emitter with a resonant frequency of 32 kHz. It was found that erosion activity rapidly decreases with distance from the emitter and depends on the distance to the emitter L as 1/L3 when the diameter of the emitter is less than or of the order of the wavelength in the used liquid. It was shown that there is a correlation between the erosion activity of cavitation and the readings of the cavitometer with the output signal being the integral intensity of the highfrequency component of the cavitation noise in the frequency range up to 10 MHz. Piezoelectric sensors were used to register cavitation noise. In particular, in liquids characterized by a higher level of erosion activity, the output signal of the cavitometer is also higher. In this case, the readings of the cavitometer change depending on the distance to the radiator as 1/L. Based on the data obtained, a method is proposed for assessing the erosion activity of cavitation by the magnitude of the intensity of cavitation noise in a cube. It is shown that this parameter is linearly related to the results of measurements of the erosional activity of cavitation. The results obtained will be used in the development of a specialized cavitometer designed to assess the erosion activity of cavitation during in vitro studies of the effect of ultrasound on cells.